Radiotherapy for Soft Tissue Sarcoma of the Proximal Lower Extremity. (11th August 2010) - Prendergast, Brendan; Fiveash, John B.; Gibbs, C. Parker; Scarborough, Mark T.; Indelicato, Daniel J.
Abstract : Soft-tissue sarcoma (STS) is a histopathologically diverse group of tumors accounting for approximately 10, 000 new malignancies in the US each year. The proximal lower extremity is the most common site for STS, accounting for approximately one-third of all cases. Coordinated multimodality management in the form of surgery and radiation is often critical to local control, limb preservation, and functional outcome. Based on a review of currently available Medline literature and professional experience, this paper provides an overview of the treatment of STS of the lower extremity with a particular focus on the modern role of radiotherapy.